Gambaran Dukungan Sosial Pada Orang Dengan Gangguan Jiwa Di Rumah Singgah Dinas Sosial Kota Surakarta - Terima Jaya Zega; Faqih Purnomosidi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Social support is defined as comfort, care, and appreciation or assistance that individuals feel from other people or groups. This study aims to identify various forms of social support for individuals suffering from mental disorders at the Surakarta City Social Service Shelter House. The research method is a qualitative approach with a focus on case studies. Information collection is done through interaction interviews and observation. The analytical approach that has been applied is thematic data analysis and the validity of the results is done by data triangulation. The results showed that the social support provided was very influential on people with mental disorders, this social support was not only from the family but from the closest people such as friends and social workers. Social support for clients is very important in people who experience mental disorders which include support in the form of emotional, appreciation, instrumental support and information support.